Measurement and Comparison of Inpatient Antibiotic Use in Five Different Hospitals in Tabriz - Saba Ghaffary, Taher Entezari Maleki, Jamshid Abdollahpor, Hadi Hamishehkar (Tabriz University of Medical Sciences, 2017)
Background: There is a relation between amounts of antibiotic uses and creation of resistant bacteria. Due to the critical role of antibiotics and increasing trend of resistance in developing countries, comprehensive methods of antibiotic use is necessary to limit the threat of resistant microorganisms. In this study we compare antibiotics consumption by Defined Daily Dose (DDD) per 100 bed-days in teaching and private hospitals during six months in Tabriz, Iran. Methods: Four university hospitals and one private hospital were included in this study. Amount of their antibiotic consumption obtained from the hospital pharmacies. Anatomical Therapeutic Chemical (ATC) code J01 was explained as defined daily doses per 100 bed-days (DDD/100) according to the ATC/DDD classification. The amount of consumption was assessed with DDD per 100 bed-days in six months. Results: Total antibacterial consumption was higher in Emam reza (119.62 DDD/100) than other hospitals. Cephalosporins were the most widely used antibiotic in all five hospitals with the total DDD per 100 bed-days of 53.74, 58.51, 46.09, 19.75 and 15.16 for Emam reza, Shohada, Sina, Shahriar and Shahid madani ,respectively. Cefazoline had highest use among cephalosporins consumption in all hospitals except Shahriar. Ciprofloxacin was among the five most used antibiotics in all hospitals. Conclusion: Although the pattern of antibacterial consumption was almost logical in different categories of hospitals, the total amount of DDD per 100 bed-days was dramatically more than developed countries. Specific strategies should be employed in infection control development and engage rational antibiotic utilization in order to reduce future resistant strains and increase antimicrobial efficacy.